Fibre saturation point of lesser-known timbers from Sabah - Sahri, Mohd Hamami; Jusoh, Mohd Zin; Ashaari, Zaidon; Apin, Ludi (Universiti Putra Malaysia Press, 1998)
The fibre saturation point (FSP) values of some 'OT' timbers from Sabah, Malaysia were evaluated. 'OT' is a term used to refer to a number of unidentified or unknown timbers and also S01ne identified lesser known timbers of Sabah. The fibre satumtion point values of these 30 species ofOT timbers mngefrom 17 - 33%. Determination of fibre salumtion point in relation to OT wood properties is very useful in timber drying, conversion and timber utilization.